ANALISIS PENDAPATAN DAN KELAYAKAN USAHA TERNAK SAPI POTONG DI DESA SUMURBER KECAMATAN PANCENG KABUPATEN GRESIK (JEB17 : Jurnal Ekonomi dan Bisnis, 2024)
Beef cattle is a very potential livestock product. Beef cattle are also one of several sources of food that have high nutritional value in people's lives. Beef cattle themselves have several benefits, including; beef for food and other by-products such as cow dung, cow skin, beef bones, and so on. This type of research is a qualitative research using Return On Investment (ROI), Revenue Cost Ratio (R/C), and Benefit Cost Ratio (B/C) calculators as indicators of the feasibility of beef cattle business. The data used in this study are primary data obtained from the results of interviews and observations with informants who have been determined in this study. The informants from this study are beef cattle breeders in Sumurber Village, Panceng District, Gresik Regency who have been in the cattle business for 1 year or more. The beef cattle business in Sumurber Village, Panceng District, Gresik Regency under study has different annual costs. The total expenditure of the six informants was then taken on average, which was IDR 52,188,000 per year during the process of fattening beef cattle. The total income of the six informants was then taken on average, which was IDR 59,462,000 per year during the process of fattening beef cattle. The results of this study are that the feasibility of beef cattle farming in Sumurber Village, Panceng District, Gresik Regency, is declared feasible by taking into account several aspects, namely the overall average B/C of beef cattle business in Sumurber Village, Panceng District, Gresik Regency, which is 1.12. The average overall R/C of beef cattle business in Sumurber Village, Panceng District, Gresik Regency is 2.13. The overall average ROI of the beef cattle business in Sumurber Village, Panceng District, Gresik Regency is 113.45%. Keywords: Beef Cattle, Cost, Income, and Business Flexsibility